2013
DOI: 10.1111/j.1552-6569.2012.00775.x
|View full text |Cite
|
Sign up to set email alerts
|

No Regional Gray Matter Atrophy Differences between Pediatric‐ and Adult‐Onset Relapsing‐Remitting Multiple Sclerosis

Abstract: Regional GM differences were not found between POMS adults and MS controls matched for age or disease duration. Although of limited sample size, these findings suggest that there are no regional GM atrophy differences between RR POMS and AOMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…On the other hand, no difference in other brain volumes was found between the two MS groups. This is in line with recent studies, where, compared with NC, voxelwise regional GM atrophy was not different between young adult POMS and AOMS ( 40 ) and the predominant atrophy in deep GM, including the thalamus, was similar in younger and older onset MS patients matched for short disease duration and clinical status ( 41 ).…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, no difference in other brain volumes was found between the two MS groups. This is in line with recent studies, where, compared with NC, voxelwise regional GM atrophy was not different between young adult POMS and AOMS ( 40 ) and the predominant atrophy in deep GM, including the thalamus, was similar in younger and older onset MS patients matched for short disease duration and clinical status ( 41 ).…”
Section: Discussionsupporting
confidence: 92%
“…To go one step further than existing clinical studies, [2][3][4][5] we analyzed GMV, a measure of neuro-axonal loss, 27 and WM FA, reflecting WM inflammation and microstructural damage. 28 Both metrics are associated with physical and cognitive impairment in MS. [27][28][29][30] Differently from previous MRI studies, [11][12][13] the physiologic effects of age and sex were removed from MRI variables by standardization on HCs, allowing assessment of the pure effect of age at onset on these variables and a reconstruction of GMV and WM FA trajectories with increasing DD.…”
Section: Discussionmentioning
confidence: 99%
“…11 Another study found WM damage in patients with POMS compared to both age-and DD-matched patients with AOMS. 12 Limitations of these and other studies [11][12][13] were confounding effects of either age or DD when adjusting for the other variable.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…14 This is corroborated by findings in a long-term follow-up study, in which no differences were seen in regional GM atrophy between age-and disease-duration-matched adult-and pediatric-onset MS patients. 15 Thus, multiple MRI studies have demonstrated clear evidence for high disease activity and progressive atrophy in individuals with pediatric onset MS.…”
Section: Increased Disease Burden In Children With Multiple Sclerosismentioning
confidence: 99%